TNFα Modulates Cardiac Conduction by Altering Electrical Coupling between Myocytes - George, Sharon A.; Calhoun, Patrick J.; Gourdie, Robert G.; Smyth, James W.; Poelzing, Steven (Frontiers in Physiology, 2017)
Background: Tumor Necrosis Factor α (TNFα) upregulation during acute inflammatory response has been associated with numerous cardiac effects including modulating Connexin43 and vascular permeability. This may in turn alter cardiac gap junctional (GJ) coupling and extracellular volume (ephaptic coupling) respectively. We hypothesized that acute exposure to pathophysiological TNFα levels can modulate conduction velocity (CV) in the heart by altering electrical coupling: GJ and ephaptic. Methods and Results: Hearts were optically mapped to determine CV from control, TNFα and TNFα + high calcium (2.5 vs 1.25 mM) treated guinea pig hearts over 90 mins. Transmission electron microscopy was performed to measure changes in intercellular separation in the gap junction-adjacent extracellular nanodomain - perinexus (WP). Cx43 expression and phosphorylation were determined by Western blotting and Cx43 distribution by confocal immunofluorescence. At 90 mins, longitudinal and transverse CV (CVL and CVT, respectively) increased with control Tyrode perfusion but TNFα slowed CVT alone relative to control and anisotropy of conduction increased, but not significantly. TNFα increased WP relative to control at 90 mins, without significantly changing GJ coupling. Increasing extracellular calcium after 30 mins of just TNFα exposure increased CVT within 15 mins. TNF + high calcium also restored CVT at 90 mins and reduced WP to control values. Interestingly, TNF+high calcium also improved GJ coupling at 90 mins, which along with reduced WP may have contributed to increasing CV. Conclusions: Elevating extracellular calcium during acute TNFα exposure reduces perinexal expansion, increases ephaptic and GJ coupling, improves CV and may be a novel method for preventing inflammation induced CV slowing.